Rent Taxation when Cost Tranfers are Possible, but Costly - H.E. Halvorsen; D. Lund (University of Oslo, Department of Economics, 1998)
While rent taxation in some theories is neutral, and the tax rate could not be set to one hundred percent to minimize the need for distortionary taxes, this does not occur in practice. An important reason for this is the transfer incentives that would result. Monitoring to prevent transfer pricing is difficult, in particular on the cost side. For dorporations, monitoring implies that both transfer pricing and real transfers will be costly. Assuming a convex cost function for cost transfers, it is shown that the optimal tax system combines a cash flow tax with a royalty, i.e., a tax on gross revenues.
Keywords: H21; H22; 330; rent; taxation; pricing; income